Pelatihan Manajemen Nyeri Non-Farmakologis untuk Kader Kesehatan di Kelurahan Jajar Surakarta - Tri Budi Santoso; Andang Sudarmono (Lembaga Pengembangan Kinerja Dosen, 2024)
Non-pharmacological pain management is an important approach to improving the quality of life of patients with chronic pain. This technique includes various methods, such as relaxation, heat and cold therapy, distraction, and deep breathing techniques, which aim to reduce the perception of pain without the need for medication. This approach is especially useful for patients who cannot or do not want to rely on pharmacological treatment. This training aims to improve the understanding and skills of health cadres in implementing non-pharmacological techniques in pain management in the community. This community service uses a quantitative method with a pre-experimental one-group pre-test and post-test design to measure changes in the understanding and skills of health cadres. Respondents consisted of 20 health cadres who lived in Jajar Village, Surakarta. The training materials included basic theories of pain management, as well as direct practice of non-pharmacological techniques. The results of the community service showed a significant increase in the understanding and skills of health cadres after being given training. This can be seen from the significant difference in pre-test and post-test scores. This increase indicates that non-pharmacological training is effective in improving the competence of health cadres, which is expected to be applied in helping patients manage pain in a safer and more efficient way.